A new model for testing green consumer behaviour. (10th January 2019) - Paço, Arminda do; Shiel, Chris; Alves, Helena
Abstract: Several green consumer behaviour models have sought to explain the relationship between green attitudes and individual behaviours interrelating with green consumption based on traditional theories. Nevertheless, there have been difficulties in developing an optimum or even a consensual model able to predict green consumer behaviour. This paper thus seeks to examine the links between a set of constructs in order to propose a model for green consumer behaviour based on a different set of buying behaviour antecedents: a prosocial attitude, the value placed on green and green communication. We developed a survey, in a self-administered questionnaire format, to gather data before applying Structural Equation Modelling (SEM) for the analysis. The results returned convey how general prosocial attitudes have a direct influence on green consumption values, and that green values positively influence green buying behaviour and receptivity to green advertising. However, green advertising generates only a weak influence on green buying behaviours. The relationship between these concepts becomes important whenever considering how best to develop green marketing campaigns and communication strategies able to further nurture green behaviours. Graphical abstract: Image Highlights: An optimum or consensual model to predict green consumer behaviour is difficult to achieve. A model for green consumer behaviour based on several constructs was developed and tested. General prosocial attitudes have a direct influence on green consumption values. Green advertising seems to positively influence buying behaviour.